Síndrome das pernas inquietas : doença comum e atormentante em pacientes dialíticos - Menezes, Andreia Freire de (2012)
Introduction: Restless Legs Syndrome (RLS) is more prevalent in chronic kidney disease patients in comparison to the general population, but its diagnosis is still delayed and predictors are unknown. Objectives: The goals of this study are to diagnose, determine the prevalence and severity of RLS and to identify independent variables associated with this disease among chronic dialysis patients. Methods: 326 chronic dialysis patients were launched in this observational and transversal study. International Study Group of Restless Legs Syndrome criterion was used to diagnosis RLS and International Scale of Degrees of Restless Legs Syndrome was used to determine its severity. Patients with and without RLS were compared using demographic and clinical characteristics, including dialysis modality. Statistical analysis was performed using Student t test and chi-square test (significance level p<0.05). Results: The median age was 50 years, 59% were men, 77% had time on dialysis >1 year and hypertension was the most common etiology (26%). RLS was diagnosed in 19.3% of patients and in 52.4% of them it was in severe forms. Patients with and without RLS were not different according to demographic, clinical and modalities characteristics. Conclusions: RLS is frequent in chronic dialysis patients and it happen in severe forms. Dialysis modality and other clinical characteristics analyzed in this sample may not have a significant effect on the diagnosis. Further studies are necessary to identify potentially predictors of RLS in this specific population.